Public investment as a solution to low growth - PARK, Eun Young (KDI School, 2016)
There are well-known obstacles of linkage between public investment and growth: infrastructure gap and efficiency gap. And the difference of efficiency between groups ofcountries by economic development level. Further, the most efficient group is twice as efficient as the least efficient group. IMF, the most authoritative institution in analyzing public investment, insisted that PIM (public investment management) is the key issue to enhance efficiency in public investment. The hypothesis of this thesis, “strengthening of PIM effects on efficiency of public investment” is proven by regression analysis but under income quartile control. The income group under the lowest 50% quartile showed that it has a lower inefficiency (i.e., higher efficiency) if its PIMI (public investment management index) is higher. Therefore, the goal of this thesis is to verify the relationship between PIM and efficiency. Moreover, it tries to find other variables that affect the efficiency of public investment. For the analysis, the dependent variable is efficiency (inefficiency score), which is assessed by the PIE-X index and the independent variable is public investment management, which is assessed by the PIMI index. To prevent some biases, this analysis input data constructed by the IMF. To differentiate the adjusted index from the original PIE-X, it is named as “Neo PIE-X” For analyzing other variables, the result of CPIA (an index similar to PIMI) was not different that of PIMI, but CPI was statistically insignificant. This suggests that the effect of corruption on public investment is not certain. The effect of strengthening PIM is stronger in low income countries than in middle income countries. This is recommendable for MDBs(Multilateral Developing Banks) to put a higher priority on strengthening PIM, when they consider public investment especially in low income countries. Neo PIE-X, is very accessible to efficiency related data. I hope that this study would be a catalyst for other studies to focus on enhancing the efficiency of public investment, following IMF’s study.
Thesis(Master) --KDI School:Master of Public Policy,2016